Partnership for health promotion as a platform to improve public health outcomes in Small Island Developing States: a case study of the Union of the Comoros - Luciani, Andrea; Abega, Sandrine; Diarra, Abdoulaye; Drameh, Pamela; Moeti, Matshidiso (Frontiers in Public Health, 2025)
In the Comoros, the World Health Organization (WHO) initiated a partnership with Civil Society Organizations (CSOs) aimed at improving health outcomes of target population. Health improvements were associated with increased service reach and selected observed changes in service indicators, reaching over 30,000 individuals (1), including women and children in underserved areas. Specific outcomes include strengthened access to selected maternal, neonatal and child health services; expanded community outreach and early detection activities relevant to noncommunicable conditions, such as oral health, women’s cancers, hypertension, diabetes, hepatitis. The collaborative approach also strengthened the capacity of CSOs to deliver health services. The WHO-CSO partnership in the Comoros demonstrates the potential of strategic collaborations to enhance health outcomes in resource-limited settings. The findings support the scalability of such initiatives across similar contexts in Africa and other small island developing states (SIDS).